A study on the correlations between acoustic speech variables and bradykinesia in advanced Parkinson's disease - Cavallieri, Francesco; Di Rauso, Giulia; Gessani, Annalisa; Budriesi, Carla; Fioravanti, Valentina; Contardi, Sara; Menozzi, Elisa; Pinto, Serge; Moro, Elena; Antonelli, Francesca; Valzania, Franco (Frontiers in Neurology, 2023)
Background: Very few studies have assessed the presence of possible correlation between speech variables and limb bradykinesia in patients with Parkinson’s disease (PD). The objective of this study was to find correlations between different speech variables and upper extremity bradykinesia in different medication conditions in advanced PD patients. Methods: Retrospective data were collected from a cohort of advanced PD patients before and after an acute levodopa challenge. Each patient was assessed with: a perceptual-acoustic analysis of speech which included several quantitative parameters (i.e. maximum phonation time [MPT]; intensity [dB]); the Unified Parkinson's Disease Rating Scale (UPDRS) (total scores, subscores and items), and a timed test (tapping test for 20 seconds) to quantify upper extremity bradykinesia. Pearson's correlation coefficient was applied to find correlations between the different speech variables and tapping rate. Results: Fifty-three PD patients (males: 34; disease duration: 10.66 [SD 4.37] years; age at PD onset: 49.81 years [SD 6.12] were included. Levodopa intake increased the MPT of sustained phonation (p<0.01) but it reduced speech rate (p=0.05). In the defined-OFF condition, MPT of sustained phonation positively correlated with both bilateral mean (p= 0.044, r-value: .299) and left (p= 0.033, r-value: .314) tapping. In the defined-ON condition, the MPT correlated positively with bilateral mean tapping (p= 0.003), left (p= 0.003) and right tapping (p= 0.008). Conclusions: This study confirms the presence of correlations between speech acoustic variables and upper extremity bradykinesia in advanced PD patients. These findings suggest common pathophysiological mechanisms.